Synthesis, Structure, and Reactivity of Ga‐Substituted Distibenes and Sb‐Analogues of Bicyclo[1.1.0]butane. Issue 50 (26th June 2017) - Tuscher, Lars; Helling, Christoph; Ganesamoorthy, Chelladurai; Krüger, Julia; Wölper, Christoph; Frank, Walter; Nizovtsev, Anton S.; Schulz, Stephan
Abstract: Monovalent gallanediyl LGa L=HC[C(Me)N(2, 6‐ i Pr2 C6 H3 )]2 reacts with SbX3 to form the Ga‐substituted distibenes [(LGaX)2 Sb2 ] (X=NMeEt1, Cl2 ). Upon heating, 2 reacts to the bicyclo[1.1.0]butane analogue [(LGaCl)2 (μ, η 1:1 ‐Sb4 )]3 containing a [Sb4 ] 2− dianion. Moreover, 2 reacts with Li amides LiNR2 in salt elimination reactions that form the corresponding amido‐substituted compounds1 and [(LGaNMe2 )2 Sb2 ]4, whereas reactions of4 and [(LGaNMe2 )2 (μ, η 1:1 ‐Sb4 )]5 with two equivalents of GaCl3 resulted in the formation of2 and3, respectively.1, 2 and3 were characterized by 1 H and 13 C NMR spectroscopy, elemental analysis, and single crystal X‐ray diffraction. In addition, their bonding situation was analyzed by quantum chemical calculations. Abstract : Gallium‐antimony compounds : LGa reacts with SbX3 to form Ga‐substituted distibenes [(LGaX)2 Sb2 ] (NMeEt1, Cl2, NMe2 4 ). Compounds2 and4 were thermally converted into the corresponding tetrastibines [(LGaX)2 (μ, η 1:1 ‐Sb4 )] (Cl3, NMe2 5 ). Salt elimination reactions of2 with Li amides yielded amido‐substituted compounds1 and4, whereas amide/chloride exchange reactions of4 and5 with GaCl3 yielded2 and3 . Quantum chemical calculations revealed the bonding situation within the complexes.